2011
DOI: 10.1093/ajae/aaq111
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Distributional Form of Farm‐Level Yields

Abstract: Representing farm-level crop yield heterogeneity and distributional form is critical for risk and crop insurance research. Most studies have used county data, understating both systematic and random variation. Comparison of systematic versus random intra-county variation is lacking. Few studies compare the various distributional forms that have been proposed. This study utilizes the extensive potential of government farm-level crop insurance data. Results show that systematic intra-county variation is surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Comparable yield distribution for the entire meta-database herein analyzed was previously documented ( Just and Weninger, 1999;Claassen and Just, 2011;Assefa et al, 2014). However, there are studies which argued that crop yields (at county scale) were not normally distributed, but instead were negatively or positively skewed (Harri et al, 2009;Hennessay, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…Comparable yield distribution for the entire meta-database herein analyzed was previously documented ( Just and Weninger, 1999;Claassen and Just, 2011;Assefa et al, 2014). However, there are studies which argued that crop yields (at county scale) were not normally distributed, but instead were negatively or positively skewed (Harri et al, 2009;Hennessay, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…This, for instance, is also the case in agricultural yield insurance applications (e.g. area yield insurance), which either frequently use aggregated (at least county-level) data or rely on observations from a few single farms (Claassen and Just, 2011). Regarding these applications, Cooper et al (2009) point out that the aggregation of crop yields causes errors in the risk assessment for farm-level analysis.…”
Section: Introductionmentioning
confidence: 99%
“…; Babcock and Hennessy ; Smith and Goodwin ). It has also been shown that subsidized insurance incentivizes producers to grow crops in places where they might not have grown them otherwise, commonly referred to as the extensive margin effect (see Wu ; Claassen and Just ; Miao et al. ).…”
Section: Unintended Consequences Of Brm Subsidizationmentioning
confidence: 99%